East Asian American cultural essentialism - Chiou, Andy Y.; Feng, Jing Betty (Frontiers in Organizational Psychology, 2024)
Introduction Past research on the “bamboo ceiling” tend to focus on the barriers it presents, with few studies examining individuals who break through the bamboo ceiling. The purpose of this study is to explain the psychological factors driving the individual differences between East Asian Americans who break through the bamboo ceiling and those who do not. Methodology This two-study sequential mixed-methods exploratory research study included 19 one-on-one semi-structured interviews and 338 survey respondents by East Asian Americans. Results In Study 1, based on 19 one-on-one semi cultural essentialism and bicultural identity integration emerged from the interview data as contributing factors. Interviewees who exhibited essentialist or social constructionist beliefs showed different behavioral and career patterns. This mediating relationship was supported in Study 2. Taken together, it was found that East Asian Americans who had less essentialist views of culture were more likely to have a fluid and integrated bicultural identity and more likely to break the bamboo ceiling in their careers. Discussion The findings from both qualitative and quantitative data suggest that having more fluid concepts of culture, associating with more integrated bicultural identities, may improve career prospects in a multicultural work environment. This article offers practical implications for Asian Americans who desire to achieve their career goals to be authentic self while remaining adaptable and developing a mindset of “flexibility.”